Impact of Children's math self-concept, math self-efficacy, math anxiety, and teacher competencies on math development. (August 2020) - Kaskens, Jarise; Segers, Eliane; Goei, Sui Lin; van Luit, Johannes E.H.; Verhoeven, Ludo
Abstract: We examined to what extent children's development of arithmetic fluency and mathematical problem-solving was influenced by their math self-concept, math self-efficacy, and math anxiety but also teacher competence, specifically: actual teaching behavior, self-efficacy, and mathematical teaching knowledge. Participants were 610 children and 31 teachers of grade four. Multi-level analyses showed children's math self-concept to be a positive predictor of arithmetic fluency and actual teaching behavior to be a negative predictor. The development of mathematical problem-solving was predicted: positively by mathematical teaching knowledge; negatively by actual teaching behavior and teachers' self-efficacy; and not at all by the child factors of math self-concept, math self-efficacy, or math anxiety. Promoting the self-confidence of young children is essential for their mathematical development. More research into the relationship between teaching behaviors and children's math development is needed. Highlights: Establishment of a solid math foundation in elementary school is critical for children's mathematical development. Attention to math self-concept of children should be part of teachers' professional development. Teachers' mathematical teaching knowledge contributes to children's mathematical development. Analyses of arithmetic fluency and mathematical problem-solving showed different outcomes.